Divergent occurrences of juvenile and adult trees are explained by both environmental change and ontogenetic effects - Heiland, Lukas; Kunstler, Georges; Ruiz‐Benito, Paloma; Buras, Allan; Dahlgren, Jonas; Hülsmann, Lisa (Ecography (Copenhagen), 2022)
Recent climate warming has fueled interest into climate‐driven range shifts of tree species. A common approach to detect range shifts is to compare the divergent occurrences between juvenile and adult trees along environmental gradients using static data. Divergent occurrences between life stages can, however, also be caused by ontogenetic effects. These include shifts of the viable environmental conditions throughout development (‘ontogenetic niche shift') as well as demographic dependencies that constrain the possible occurrence of subsequent life stages. Whether ontogenetic effects are an important driver of divergent occurrences between juvenile and adult trees along large‐scale climatic gradients is largely unknown. It is, however, critical in evaluating whether impacts of environmental change can be inferred from static data on life stage occurrences. Here, we first show theoretically, using a two‐life stage simulation model, how both temporal range shift and ontogenetic effects can lead to similar divergent occurrences between adults and juveniles (juvenile divergence). We further demonstrate that juvenile divergence can unambiguously be attributed to ontogenetic effects, when juveniles diverge from adults in opposite direction to their temporal shift along the environmental gradient. Second, to empirically test whether ontogenetic effects are an important driver of divergent occurrences across Europe, we use repeated national forest inventories from Sweden, Germany and Spain to assess juvenile divergence and temporal shift for 40 tree species along large‐scale climatic gradients. About half of the species‐country combinations had significant juvenile divergences along heat sum and water availability gradients. Only a quarter of the tree species had significant detectable temporal shifts within the observation period. Furthermore, significant juvenile divergences were frequently associated with opposite temporal shifts, indicating that ontogenetic effects are a relevant cause of divergent occurrences between life stages. Our study furthers the understanding of ontogenetic effects and challenges the practice of inferring climate change impacts from static data.